Advancing soil-structure interaction (SSI): a comprehensive review of current practices, challenges, and future directions - Najar, Imtiyaz Akbar; Ahmadi, Raudhah; Amuda, Akeem Gbenga; Mourad, Raghad; Bendary, Neveen El; Ismail, Idawati; Abu Bakar, Nabilah; Tang, Shanshan (Springer Nature, 2025)
The safety, stability, and long-term performance of reinforced concrete (RC) structures depend significantly on soil-structure interaction (SSI), a critical phenomenon governing the dynamic relationship between soil and structural behaviour. SSI plays a pivotal role in seismic design, influencing the stiffness, damping, and natural frequency of structures, yet its application in practical design remains underutilized due to challenges in modelling and integrating code provisions. This review synthesizes existing knowledge on SSI, emphasizing its impact on buildings, bridges, and foundations under static and dynamic loads. It highlights advancements in analytical, numerical, and experimental modelling methods, such as finite element analysis and discrete element methods, and evaluates their effectiveness in capturing the complex interactions between soil and structural systems. The review identifies key gaps, including a lack of unified guidelines in international codes, inadequate integration of SSI in real-world design processes, and limited exploration of its role in emerging engineering challenges like sustainability and climate resilience. Historical seismic events, such as the Kobe and Loma Prieta earthquakes, are analysed to underscore the detrimental consequences of neglecting SSI considerations. Additionally, the review discusses recent innovations, including the application of machine learning and advanced computational tools, and their potential to enhance the accuracy and efficiency of SSI analysis. This study offers actionable insights for improving design practices, such as adapting SSI frameworks for structures on soft soils and incorporating dynamic interactions in seismic design codes. It concludes with a call for interdisciplinary collaboration and future research into novel SSI applications, including its integration with smart sensing technologies and sustainable infrastructure design. This review bridges the gap between theoretical advancements and practical applications of soil-structure interaction (SSI) by synthesizing current knowledge, identifying critical research gaps, and proposing innovative solutions to enhance structural resilience, sustainability, and seismic safety.